Calibrated automated thrombin generation in normal uncomplicated pregnancy - Rosenkranz, Andrea; Hiden, Michael; Leschnik, Bettina; Eva-Christine, Weiss; Schlembach, Dietmar; Lang, Uwe; Gallistl, Siegfried; Muntean, Wolfgang (Thrombosis and Haemostasis, 2008)
Pregnancy is associated with substantial changes in the haemostatic system and a six-fold higher incidence of venous thromboembolism. Conventional global tests, such as prothrombin time and activated partial thromboplastin time, do not definitely detect this hypercoagulable condition. We investigated whether the changes in haemostatic system during pregnancy are reflected in the calibrated automated thrombography (CAT). Thrombin generation was measured in platelet-poor plasma (PPP) of 150 healthy pregnant women without any pregnancy associated diseases by means of CAT. In addition, prothrombin (FII), antithrombin (AT), protein S, protein C, tissue factor pathway inhibitor (TFPI), plasminogen activator inhibitor-1 (PAI-1), thrombin-antithrombin complex (TAT), and prothrombin fragments 1+2 (F1+2) were measured. Endogenous thrombin potential (ETP) and peak of thrombin generation increased significantly with gestational weeks, while lag time and time to peak remained unchanged. A significant increase of PAI-1,TFPI,F1+2 and TAT as well as a significant decrease of free protein S, protein S antigen, and protein S activity was observed. Levels of AT and protein C remained stable during pregnancy. Division of population in trimester of pregnancy and analysis of differences between the trimesters showed rather similar results. Our study shows that endogenous thrombin potential does increase with duration of normal uncomplicated pregnancy. Whether parameters of continuous thrombin generation will correlate with thrombembolic disease remains to be shown.
Keywords: Calibrated automated thrombography; endogenous thrombin potential; pregnancyw; pregnancy; thrombin generation